On the job online harrasment and its effects on Filipino journalists and the journalism practice - Laguna, Mekaella Irish Francisco; Tangi, Lucia P. (Quezon City College of Mass Communication, University of the Philippines, 2023)
Journalists are under attack in the Philippines, and while more overt types of attacks such as legal and physical attacks have been closely studied and documented in the country, online harassment and abuse on social media is not. With the rise of reported cases of journalists being attacked on social media, this thesis will examine how Filipino journalists experience online harassment, how it affects them and their professional practice as well as their coping strategies. This study also examines how newsrooms have or have not responded to online harassment, and what institutional interventions are needed to combat this risk. Studied under the lens of cognitive dissonance theory, 41 Filipino journalists from various local and international news organizations completed a survey questionnaire to generate the data needed. It found that on average, journalists in the Philippines experience online harassment sometimes in a month, often in the form of work-related insults. Female journalists are more likely to experience sexual threats than male journalists and while journalists are inclined to ignore harassment, steps are still taken to alleviate their online experience. Most of the journalists follow Festinger's suggestion of changing one's environment to minimize cognitive dissonance in coping with online harassment. While interventions are present in some news organizations, most of the responsibility in dealing with online harassment is left to the journalists. There is also an industry lack in concrete mental health support for journalists outside mental health seminars. Philippine journalists also see the need in having an industry safety guide to help them navigate the online sphere.
Vita
Thesis
Includes bibliographical references (pages 63-68) and appendices (pages 69-72).
Keywords: Journalists -- Philippines; Online hate speech -- Philippines; Journalists—Job stress -- Philippines